Community art: origin and evolution of collaborative artistic practices - Palacios Garrido, Alfredo (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2009)
This article revises the meaning of the term community art, coined in the 1970s to describe a series of artistic practices that involved public collaboration and participation in an attempt to reach social improvement through art. It is described in the context of the 70s, and the social and artistic philosophies that it is based on. Particularly two: the importance of the social context of the piece and the involvement of the viewer. Community art evolves towards institutional and educational areas in the following years and becomes a point of reference for contemporary public art. To conclude the main problematic associated to collaborative artistic practices are described.